(untitled) - Neher, Clark D. (DeKalb, 2000)
This book introduction provides an engaging at the history, culture, and politics of thisc intriguing region. Intended for both high school students and beginning undergaduates, the book is also useful background reading for upper divison courses and for general readers new to the study of Sountheast Asia.
Keywords: Southeast Asia,Đông Nam Á